2001
DOI: 10.1021/ac001268b
|View full text |Cite
|
Sign up to set email alerts
|

UV Raman Spectral Intensities of E. Coli and Other Bacteria Excited at 228.9, 244.0, and 248.2 nm

Abstract: Resonance Raman spectral intensities per average bacterial cell have been measured quantitatively for Gram-negative Escherichia coli, Citrobacter freundii, and Enterobacter aerogenes, as well as Gram-positive Bacillus subtilis and Staphylococcus epidermidis. Spectra have been obtained from cultures in the lag, log, and stationary growth phases excited in turn by 228.9, 244.0, and 248.2 nm light. Although Raman spectral peak positions (cm(-1)) excited by a given wavelength are very similar for all five bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
79
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 40 publications
9
79
0
Order By: Relevance
“…22 The method is also used for cellular level analysis: using resonance, DUV can selectively observe such aromatic compounds in a cell. [23][24][25] Cellular conditions, 26 types, 27 and metabolic states 28 have all been studied using DUV Raman, and these aromatic compounds play important roles in dynamic activities and functions of cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…22 The method is also used for cellular level analysis: using resonance, DUV can selectively observe such aromatic compounds in a cell. [23][24][25] Cellular conditions, 26 types, 27 and metabolic states 28 have all been studied using DUV Raman, and these aromatic compounds play important roles in dynamic activities and functions of cells.…”
mentioning
confidence: 99%
“…27 We chose the band at 1490 cm −1 for cellular nucleotide imaging. The distribution of the intensity at 1490 cm −1 is shown in Fig.…”
mentioning
confidence: 99%
“…In contrast, a detection method that has minimal preparatory sequences and has been used for on-chip detection is spectroscopy, such as infrared ͑IR͒, ultraviolet and visible ͑UV-Vis͒ and Raman spectroscopy. [31][32][33] IR and Raman spectroscopy measure the vibrational modes of the molecules and the various structures, thus providing a detailed spectrum. 34 In particular, Raman spectroscopy can often show bonds that are undetectable through IR, thus, it has been shown to be extremely specific to each bacterium, where each spectrum can act as a fingerprint.…”
mentioning
confidence: 99%
“…Pioneering work by Naumann et al (1991aNaumann et al ( , 1991b showed that IR and Raman spectroscopy can be used to classify bacteria and yeasts. Using deep UV excitation (e.g., 244 nm), direct investigation of macromolecules such as DNA or proteins becomes possible due to resonant enhancement (e.g., Manoharan et al, 1990;Chadha et al, 1993;Wu et al, 2001;Jarvis and Goodacre, 2004). Storrie-Lombardi et al (2001) and Tarcea et al (2007) showed that Raman excitation wavelengths in the deep UV region are able to selectively enhance Raman signals of proteins and DNA=RNA.…”
Section: Accepted Biogenic Raman Spectral Signaturesmentioning
confidence: 99%